Increasing Appearance of Reassortant Influenza B Virus in Taiwan from 2002 to 2005 - Tsai, Huey-Pin (American Society for Microbiology, 2006)
Genetic and antigenic analyses of influenza B virus field strains isolated in Taiwan from 1998 to 2005 were performed. To investigate the molecular evolution of influenza B viruses, sequence analysis of the hemagglutinin (HA1 subunit) and neuraminidase genes was performed. All influenza B viruses isolated between 1998 and 2000 belonged to the B/Yamagata/16/88 lineage. The B/Victoria/2/87 lineage, which was cocirculating with the Yamagata lineage, was identified in Taiwan in March 2001. Concurrently, there was an increasing prevalence of this lineage in many parts of the world, including North America and Europe, during the 2001-2002 season. Since 2002, genetic reassortants of influenza B virus with the Victoria lineage of hemagglutinin and the Yamagata lineage of neuraminidase have been found at a rate of 46%. Therefore, in 2002, at least three sublineages of influenza B virus strains, the B/Shanghai/361/2002-like strain (Yamagata lineage), the B/Hong Kong/330/01-like strain (Victoria lineage), and the B/Hong Kong/1351/02-like strain (B reassortant lineage), were identified in Taiwan. The results showed that genetically distinct lineages can cocirculate in the population and that the reassortment among these strains plays a role in generating the genetic diversity of influenza B viruses. Interestingly, from January to April 2005, B reassortant viruses became dominant (73%) in Taiwan, which indicated that a mismatch had occurred between the influenza B vaccine strain recommended for the 2004-2005 season in the Northern hemisphere by the World Health Organization and the epidemic strain.